A Conceptual Framework for Evaluating Construction Safety Awareness Using Virtual Safety Games - Thapa, Sabnam; Peansupap, Vachara (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
The construction industry is considered one of the most dangerous jobs globally, and lack of safety awareness is a major cause of accidents. Therefore, it is essential to evaluate the level of safety awareness among construction personnel at the site. Past research attempts evaluated safety awareness levels based on passive methods such as questionnaires and interviews, but these are self-evaluated and do not assess the ability of the person to apply safety knowledge in real-world scenarios. Recently, Virtual Reality (VR) games have been widely recognized for their applications in safety education and training and have been effectively used to assess safety knowledge, attitude, and hazard inspection. This research aims to develop a framework for assessing the existing level of safety awareness using VR games. The Input-Process-Output (IPO) model has been a popular game design model with improvements in components of game characteristics in the newer IPO models. Based on the ideology of these methods, a new conceptual framework was developed to assess safety awareness, which consists of safety knowledge and hazard detection as indicators. The details of steps involved in developing the key components of game design are explained in detail. In this research, safety awareness has been recognized in terms of safety knowledge and hazard detection. Player performance is reflected in each indicator; therefore, it provides clarity on the areas of awareness in which players lack or excel and can be managed accordingly. Thus, this framework can be used as a guideline in the development of assessment tools for safety awareness with VR games.